PENGARUH OPINI AUDIT MODIFIKASI TERHADAP KEPUTUSAN PIN-JAMAN DAN KEPUTUSAN INVESTASI - Sarwendah, Vincensia; Lasdi, Lodovicus; Tedjasuksmana, Budianto (Jurnal Akuntansi Kontemporer, 2017)
The objective of this study was to examine whether the effect of the modified audit opinion of loans received by the company's decision and the decision of investment expenditure by the company. Design research is quantitative research with the hypothesis. The sample used in this study are manufacturing companies that listed in Indonesia Stock Exchange with a four year study period from 2011-2014. The independent variable of this study is a modified audit opinion, while the dependent variable is the financial constraints represented by the decision of the loan and investment decisions. The results from this study indicate that in 2011-2014, for overall modified audit opinion does not affect the decision-making loans to companies and corporate investment spending. However, an unqualified audit opinion with an explanation of the going concern paragraph affect tothe loan or investment decision because of corporate business con-tinuity uncertainty.Stable economic conditions and the majority shareholder also can determine the effect of modified audit opinion of loans and investment decisions.